Kajian Ayat-Ayat Al-Qur’an yang Berhubungan dengan Membangun Etos Kerja - Hikmatullah Jamud (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2019)
We rolled it out during the glory and destruction of people so that they could get a lesson (QS.3: 40). The progress and setback of a nation will be determined by the work ethic of the nation itself, a nation will advance when it has a good work ethic, the Qur'an offers man how to work well and correctly? Which brings good luck not only in the world but also to the hereafter. in the writing of this writing, it will be explained verses that give the motivator to work and verses that direct how to work properly and correctly.